Implementasi Framework Cobit 5 pada Audit Sistem Informasi Persediaan PT Kawat Lancar Sejahtera Murni - Narti Narti; Hariani; Fuad Nur Hasan; Rangga Pebrianto (Evolusi : Jurnal Sains dan Manajemen, 2025)
Abstract - PT Kawat Lancar Sejahtera Murni has implemented the use of technology to support the storage system of goods in the warehouse, but PT Kawat Lancar Sejahtera Murni has never conducted an persediaan information technology audit to determine whether the system is effective and efficient. PT Kawat Lancar Sejahtera Murni does not have maximum IT control causing losses to the company including loss of goods, inaccuracy due to errors in data processing, so that data integrity is in doubt. Therefore, the analysis and design of the information system audit using the Cobit 5 framework to formulate IT performance and process maturity levels is the basis for making research. The subdomains selected in this study are EDM01, EDM02, EDM03, EDM04, EDM 05, DSS01, DSS03 and DSS04. Based on the calculation results of the EDM01 subdomain 1.01, the EDM02 subdomain has a distance of 0.30, the EDM03 subdomain has a distance of 0.83, the EDM04 subdomain has a distance of 0.33, the EDM05 subdomain has a distance of 0.83, the DSS01 subdomain has a distance of 0.70, the DSS03 subdomain has a distance of 0.63 and in the DSS04 subdomain there is a distance of 0.60. Based on the results of the analysis, several suggestions can be submitted, namely PT Kawat Lancar Sejahtera is advised to consider and implement the recommendations that have been put forward in each subdomain in this study.